English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

solve the equation...
(3(x+2) -3) / 3 = 6

in word terms: 3(x+2) divided by three and equal to six

2007-10-30 10:37:06 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

(3(x+2)-3) = 18
3x+6-3=18
3x+3=18
3x=15
x=5

2007-10-30 10:48:50 · answer #1 · answered by randomdude 3 · 0 0

Okay, so we have:

(3(x+2)-3) / 3 = 6.

[Note: You left out the "minus 3" in your words definition. :)]

We first want to get rid of our fraction. If we multiply both sides by the denominator (3), it elimnates the fraction and gives us;

(3(x+2)-3) = 6(3). Or,
(3(x+2)-3) = 18. Now we can drop our parenthesis to get:
3(x+2)-3 = 18.

We want to add 3 to both sides, which gives us:

3(x+2) = 21. Now, dividing by 3, we get:
(x+2) = 7. Again, we can drop parenthesis to get:
x + 2 = 7. Subtracting, we get
x = 7 - 2 = 5

2007-10-30 17:43:04 · answer #2 · answered by twigg1313 3 · 0 0

Hello,

Cancel out the 3 on the left side giving us

x+2 -1 = 6 so x +1 = 6 and then x = 5.


Hope This Helps!

2007-10-30 17:42:42 · answer #3 · answered by CipherMan 5 · 1 1

(3(x+2) -3) / 3 = 6

"undo" the fraction by multiplying both sides by 3 to get

(3(x+2) -3) = 18

then follow order of operations (BEDMAS)

(3x+6 -3) = 18

combine like terms

3x + 3 = 18

move terms with variables to one side, constants to the other side

3 x = 15

divide by the coefficient of the variable (3)

x = 5

2007-10-30 17:45:34 · answer #4 · answered by golfingcanuck2001 2 · 0 0

Question:

3(x+2) - 3
------------- = 6
 3

Answer:

3x + 6 - 3 = 3*6
3x + 3 = 18
3x = 18 - 3
3x = 15
x = 15/3
x = 5

2007-10-30 17:46:56 · answer #5 · answered by Anonymous · 0 0

(3(x+2) -3) / 3 = 6
3x + 6 - 3 = 18
3x = 15
x = 5

2007-10-30 17:44:17 · answer #6 · answered by CPUcate 6 · 0 0

fedest.com, questions and answers